An evaluation of the group approach to alleviate rural poverty through the change agent programme : a case study of Mihintale Division, North Central Province, Sri Lanka - Pallegedara, Cyril; Dias, Hiran D.; Weber, Karl E.; Lund, Ragnhild; Swedish International Development Authority (SIDA) (Bangkok : Asian Institute of Technology, 1993)
This study is a reflection of the alternative Rural Development Approach known as the Change Agent Programmer "CAP" implemented in Sri Lanka as a participatory strategy for self-reliant development among the rural poor. It involves comparison of performance of the CAP group members (Experimental group) with that of the non-group members (Control) to ascertain the effectiveness of the CAP in improving the living conditions of the target population. For this purpose this study area was Mihintale Division in North Central Province of Sri Lanka where the CAP is in operation since 1987. The comparison included assessing their participation in rural community organizations, Their managerial capabilities, adoption of improved production technologies, access to government services and subsidies, personal and group savings, resource mobilization, etc. The required information was gathered from secondary and primary sources through literature review, field survey, observations and discussions with the beneficiaries as well as control group members and others connected with this programme. Statistical test were done to establish the significance of difference between the two groups. The study found that there is a significant difference between the two groups with regard to awareness and improving living conditions. This was mainly due to effect of the CAP intervention process, on the experimental group. Although the CAP is effectively involved with poverty alleviating activities in the country, this study suggests ways and means of strengthening and expanding the programme to benefit a large number of the poor in the rural areas.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of science
Thesis (M.Sc.) - Asian Institute of Technology, 1993
Keywords: Rural poor -- Sri Lanka; Rural development -- Sri Lanka